A study on the use of acupoint catgut embedding in the treatment of pre-diabetes: a meta-analysis and data mining approach - Yu, Yunfeng; Xu, Xuan; Tan, Danni; Yin, Yuman; Yang, Xinyu; Yu, Rong (Frontiers in Public Health, 2023)
Objective The efficacy of acupoint catgut embedding (ACE) for the treatment of pre-diabetes remains controversial. Therefore, this study investigated the clinical efficacy and acupoint selection in ACE for the treatment of pre-diabetes. Methods Eight common databases were searched for relevant literature on ACE for pre-diabetes. Meta-analysis was used to evaluate its efficacy and safety, and data mining was used to explore the protocol for acupoint selection. Results The meta-analysis revealed that compared with conventional treatment alone, conventional treatment combined with ACE reduced the levels of glycated hemoglobin A1c [mean difference (MD) −0.45, 95% confidence interval (CI) −0.67 to −0.24%, p < 0.001], fasting blood glucose (MD −0.61 mmol/L, 95% CI −0.87 to −0.36 mmol/L, p < 0.001), 2-h postprandial glucose (MD −0.77 mmol/L, 95% CI −0.98 to −0.55 mmol/L, p < 0.001), total cholesterol (MD −0.37 mmol/L, 95% CI −0.74 to 0.00 mmol/L, p = 0.049), triglyceride (MD −0.49 mmol/L, 95% CI −0.77 to −0.20 mmol/L, p < 0.001) and low-density lipoprotein cholesterol (MD −0.23 mmol/L, 95% CI −0.33 to −0.12 mmol/L, p < 0.001), and increased high-density lipoprotein cholesterol levels (MD 0.16 mmol/L, 95% CI 0.05 to 0.27 mmol/L, p = 0.004), whereas changes in the body mass index and the adverse event rates were comparable between groups. Data mining revealed that Pishu (BL20), Weiwanxiashu (EX-B3), Zusanli (ST36), Shenshu (BL23), Sanyinjiao (SP6), Weishu (BL21), and Taixi (KI3) were the core acupoints used in ACE for pre-diabetes. Conclusion ACE can effectively improve blood glucose and lipid levels in pre-diabetes patients and has a good safety profile. ACE consisting of Pishu (BL20), Weiwanxiashu (EX-B3), Zusanli (ST36), Shenshu (BL23), Sanyinjiao (SP6), Weishu (BL21), and Taixi (KI3), is a promising complementary strategy for the treatment of pre-diabetes.